Inhibition of histone deacetylase (HDAC) by 4-phenylbutyrate results in increased junctional conductance between rat corpora smooth muscle cells - Wang, Hong Zhan; Rosati, Barbara; Gordon, Chris; Valiunas, Virginijus; McKinnon, David; Cohen, Ira S.; Brink, Peter R. (Frontiers in Pharmacology, 2015)
4-phenylbutyrate (4-PB) has been shown to increase the protein content in a number of cells types. One such protein is Connexin43 (Cx43). We show here that 4-phenylbutyrate exposure results in significantly elevated cell to cell coupling, as determined by dual whole cell patch clamp. Incubation with 5 mM 4PB for 24 hours or more nearly doubles junctional conductance. Interestingly, mRNA levels for Cx43 declined with exposure to 4-PB at the 48 hour time point while western blot analysis revealed not significant change in protein levels. These data are most consistent with stabilization of the existing Cx43 pool or alterations in the number of functional channels within an existing pool of active and silent channels. These data represent a baseline for testing the efficacy of increased connexin mediated coupling in a variety of multicellular functions including erectile function.